YIA3: ADAMTS7 CLEAVAGE AND VASCULAR SMOOTH MUSCLE CELL MIGRATION IS AFFECTED BY A CORONARY ARTERY DISEASE ASSOCIATED VARIANT. (24th May 2013) - Pu, X; Xiao, Q; Kiechl, S; Chan, K; Ng, F L; Gor, S; Poston, R N; Fang, C; Patel, A; Senver, E C; Shaw-Hawkins, S; Willeit, J; et al.
Abstract : Background: Recently, genome-wide association studies have revealed an association between single-nucleotide-polymorphisms (SNPs) in a genomic region containing the ADAMTS7 (a disintegrin-like and metalloprotease with thrombospondin type 1 motif, 7) gene and susceptibility to coronary artery disease (CAD). However, it has remained unclear as to what biological mechanisms underlie this genetic association. We sought to assess possible functional effects of the non-synonymous SNP rs3825807, an adenine (A) to guanosine (G) change that results in a serine (Ser) to proline (Pro) substitution in the propeptide domain of the ADAMTS7 protein, as the G allele of this SNP has been shown to be associated with reduced risk of CAD. Methods and Results: In a population-based, prospective study, we observed an inverse relationship between the rs3825807 G allele and prevalence and severity of carotid atherosclerosis determined by carotid ultrasound (Table 1 ). In immunohistochemical analyses of coronary and carotid atherosclerotic plaques, we detected the presence of ADAMTS7 within and around smooth muscle cells in the plaques, particularly in areas near the border between the intima and media (Figure 1 A). In studies of primary cultures of vascular smooth muscle cells (VSMCs) from different individuals, we found that VSMCs of the G/G genotype had a lower migratory ability than VSMCs of the A/A genotype (Figure 1 B). We also found that conditioned media of VSMCs of the G/G genotype contained less of the cleaved form of thrombospondin-5 (Figure 1 C), an ADAMTS7 substrate that had been shown to be produced by VSMCs and inhibit VSMC migration. Furthermore, we found that media conditioned by VSMCs of the G/G genotype had lower amounts of cleaved ADAMTS7 propeptide (Figure 1 D). To further assess the effect of the Ser-to-Pro substitution on ADAMTS7 propeptide domain cleavage, we transfected cultured HEK293 cells with a plasmid for expressing either ADAMTS7-214Ser or ADAMTS7-214Pro, and then determined the relative amounts of the cleaved and uncleaved forms of ADAMTS7 propeptide in conditioned media. In these experiments, we found that media conditioned by cells transfected with the ADAMTS7-214Pro plasmid had less cleaved ADAMTS7 propeptide than media conditioned by cells transfected with the ADAMTS7-214Ser plasmid. Conclusion: The results of our study indicate that the CAD-associated SNP rs3825807 has a functional effect on ADAMTS7 maturation, thrombospondin-5 cleavage and VSMC migration, with the G allele associated with protection from atherosclerosis and CAD rendering a reduction in ADAMTS7 function.